Wnt5a induces Ryk-dependent and -independent effects on callosal axon and dendrite growth. (February 2014) - Clark, Charlotte E. J.; Richards, Linda J.; Stacker, Steven A.; Cooper, Helen M.
Abstract The non-canonical Wnt receptor, Ryk, promotes chemorepulsive axon guidance in the developing mouse brain and spinal cord in response to Wnt5a. Ryk has also been identified as a major suppressor of axonal regrowth after spinal cord injury. Thus, a comprehensive understanding of how growing axons and dendrites respond to Wnt5a-mediated Ryk activation is required if we are to overcome this detrimental activity. Here we undertook a detailed analysis of the effect of Wnt5a/Ryk interactions on axonal and dendritic growth in dissociated embryonic mouse cortical neuron cultures, focusing on callosal neurons known to be responsive to Ryk-induced chemorepulsion. We show that Ryk inhibits axonal growth in response to Wnt5a. We also show that Wnt5a inhibits dendrite growth independently of Ryk. However, this inhibition is relieved when Ryk is present. Therefore, Wnt5a-mediated Ryk activation triggers divergent responses in callosal axons and dendrites in the in vitro context.